Creativity and Leadership in the Creative Industry: A Study From the Perspective of Social Norms - Du, Xiaomin; Zhang, Hong; Zhang, Shiying; Zhang, Ao; Chen, Beibei (Frontiers in Psychology, 2021)
Individual creativity has been the focus of long-term research in creative industries. However, few studies have explored the impact on individual creativity from social factors. At the same time, the influence of individual creativity on the existence of subsequent factors in the creative industry is also worthy of further investigation. From a social perspective, this research aims to explore how social norms affect individual creativity, and how individual creativity affects subsequent leadership. The present research takes creative entrepreneurs in creative enterprises as the research objects, and the structural equation model is used to analyze the data obtained from 202 valid questionnaires. Besides, the mediating effect of individual creativity between social norms and individual leadership is verified. The results show that social norms can effectively promote the generation of individual creativity that has a positive impact on both transactional or transformational leadership. It is revealed that social norms are effective tools for enhancing creativity, answering the question of how creative ideas are transformed into creative work and leadership. Individual creativity plays a mediating role between social norms and individual leadership.